Political transitions in dominant party systems : learning to lose - Friedman, Edward, 1937-; Wong, Joseph, 1973- (Abingdon, Oxon : Routledge, 2008)
Using country-specific case studies, analysts in the field focus on the lessons that dominant parties might learn from losing and the adaptations they consequently might make in order to survive, to remain competitive or to ultimately re-gain power.
Learning to lose : dominant parties, dominant party systems, and their transitions / Edward Friedman and Joseph Wong -- Congress learns to lose : from a one-party dominant to a multiparty system in India / Susanne Hoeber Rudolph and Lloyd I. Rudolph -- A house divided against itself : the PRI's survival strategy after hegemony / Frederico Estez, Alberto Dz-Cayeros and Beatriz Magaloni -- Maintaining KMT dominance : party adaptation in authoritarian and democratic Taiwan / Joseph Wong -- The master is gone, but does the house still stand? The fate of single-party systems after the defeat of single parties in West Africa / Cric Jourde -- The communist exit in East Central Europe and its consequences / Anna Grzymala-Busse -- Learning to lose is for losers : the Japanese LDP's reform struggle / T.J. Pempel -- Embracing defeat : the KMT and the PRI after 2000 / Tun-jen Cheng -- Learning to lose (and sometimes win) : the neocommunist parties in post-Soviet politics / John Ishiyama -- Defeat in victory, victory in defeat : the Korean conservatives in democratic consolidation / Byung-Kook Kim -- Learning to lose, learning to win : government and opposition in South Africa's transition to democracy / Antoinette Handley, Christina Murray and Richard Simeon -- Learning to lose? Not if UMNO can help it / Diane K. Mauzy and Shane J. Barter -- Singapore'exceptionalism'? Authoritarian rule and state transformation / Garry Rodan -- Why the dominant party in China won't lose / Edward Friedman -- Dominant parties and democratization : theory and comparative experience / Laurence Whitehead.
Includes bibliographical references and index.
Keywords: Political parties -- Cross-cultural studies; One-party systems -- Cross-cultural studies